Novel Genotypes of Nidicolous Argas Ticks and Their Associated Microorganisms From Spain - Palomar, Ana M.; Veiga, Jesús; Portillo, Aránzazu; Santibáñez, Sonia; Václav, Radovan; Santibáñez, Paula; Oteo, José A.; Valera, Francisco (Frontiers in Veterinary Science, 2021)
The knowledge of the distribution, richness and epidemiological importance of soft ticks of the genus Argas is incomplete. In Spain, five Argas species have been recorded, including three ornitophilic nidicolous ticks, but their associated microorganisms remain unknown. This study aimed to investigate ticks from bird nests and their microorganisms. Ticks were collected extensively from natural cavities and nest-boxes used by European rollers (Coracias garrulus) and little owls (Athene noctua) in Southeastern and Central Spain. Ticks were morphologically and genetically identified and corresponding DNA/RNA tick extracts were analysed [individually (n=150) or pooled (n=43)] using specific PCR assays for bacteria (Anaplasmataceae, Bartonella, Borrelia, Coxiella/Rickettsiella and Rickettsia spp.), viruses (Flaviviruses, Orthonairoviruses and Phenuiviruses) and protozoa (Babesia/Theileria spp.). Six Argas genotypes were identified, of which only those of Argas reflexus (n=8) were identified to the species level. Two other genotypes were closely related to each other and to Argas vulgaris (n=83) and Argas polonicus (n=33), respectively. These two species have not been previously reported from Western Europe. Two additional genotypes (n=4) clustered with Argas persicus, previously reported in Spain. The remaining genotype (n=22) showed low sequence identity with any Argas species, being most similar to the African Argas africolumbae. The microbiological screening revealed infection with a rickettsial strain belonging to Rickettsia fournieri and Candidatus Rickettsia vini group in 74.7% of ticks, mainly comprising ticks genetically related to A. vulgaris and A. polonicus. Other tick endosymbionts belonging to Coxiella, Francisella and Rickettsiella species were detected in ten, one and one tick pools, respectively. In addition, one Babesia genotype, closely related to avian Babesia species, was found in one tick pool. Lastly, Anaplasmataceae, Bartonella, Borrelia, and viruses were not detected. In conclusion, five novel Argas genotypes and their associated microorganisms with unproven pathogenicity are reported for Spain. The re-use of nests between and within years by different bird species appears to be ideal for the transmission of tick-borne microorganisms in cavity-nesting birds of semiarid areas. Further work should be performed to clarify the taxonomy and the potential role of soft Argas ticks and their microorganisms in the epidemiology of zoonoses.